Colloidal 2D PbSe nanoplatelets with efficient emission reaching the telecom O-, E- and S-band. Issue 2 (20th December 2021) - Klepzig, Lars F.; Biesterfeld, Leon; Romain, Michel; Niebur, André; Schlosser, Anja; Hübner, Jens; Lauth, Jannika
Abstract : Colloidal two-dimensional (2D) lead selenide nanoplatelets with band gaps tunable by their lateral size for near- and short wave-infrared applications reaching the telecom O-, E- and S-band. Abstract : Colloidal two-dimensional (2D) lead chalcogenide nanoplatelets (NPLs) represent highly interesting materials for near- and short wave-infrared applications including innovative glass fiber optics exhibiting negligible attenuation. In this work, we demonstrate a direct synthesis route for 2D PbSe NPLs with cubic rock salt crystal structure at low reaction temperatures of 0 °C and room temperature. A lateral size tuning of the PbSe NPLs by controlling the temperature and by adding small amounts of octylamine to the reaction leads to excitonic absorption features in the range of 1.55–1.24 eV (800–1000 nm) and narrow photoluminescence (PL) reaching the telecom O-, E- and S-band (1.38–0.86 eV, 900–1450 nm). The PL quantum yield of the as-synthesized PbSe NPLs is more than doubled by a postsynthetic treatment with CdCl2 ( e.g. from 14.7% to 37.4% for NPLs emitting at 980 nm with a FWHM of 214 meV). An analysis of the slightly asymmetric PL line shape of the PbSe NPLs and their characterization by ultrafast transient absorption and time-resolved PL spectroscopy reveal a surface trap related PL contribution which is successfully reduced by the CdCl2 treatment from 40% down to 15%. Our results open up new pathways for a direct synthesis and straightforward incorporation of colloidal PbSe NPLs as efficient infrared emitters at technologically relevant telecom wavelengths.